Kecerderdasan Emosi, Kecerdasan Spiritual dan Perilaku Prososial Santri Pondok Pesantren Nasyrul Ulum Pamekasan - Sabiq, Zamzami (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. The purpose of this research was to examine the relations between emotional intelligent and spiritual intelligent with pro-social behavior. The subjects of the study were 175 students of Pondok Pesantren Nasyrul Ulum Pamekasan, consist of 96 boys and 79 girls. Data were collected by scales of emotional intelligent, spiritual intelligent, and pro-social behavior. The data analysis usedÂ  multiple regression analysis and then correlations. Results of multiple regression analysis showed that the emotional intelligent and spiri-tual intelligent have a significant relation with prosocial behavior. The result of correlation analyses between either emotional intelligence or spiri-tual intelligence with prosocial behavior showed a positive correlation signify-cantly. Variables of emotional intelligent and spiritual intelligent give effect-tive contribution toward prosocial behavior about 55,1%. Key words: pro-social behavior, emotional intelligent, spiritual intelligent